Ananda Devi and Dany Laferrière: The Culture Industry, Poverty Discourse, and Postcolonial Literatures in French - Benedicty-Kokken, Alessandra (FRAME, Journal of Literary Studies, 2026)
In response to Sandra Ponzanesi’s call to devise better tools of analysis for understanding how postcolonial literature operates as both commodity and aesthetic, this article claims that one of the roles of the postcolonial novel in the early twenty-first century is to counter the notion that culture and poverty exist in a cause-effect relationship. Drawing on novels by Ananda Devi and Dany Laferrière, this article considers how using poverty as a category of analysis might allow us as readers to better understand more recent dynamics of the literary postcolonial culture industry.